Street Light Outages, Public Safety and Crime Attraction - Chalfin, Aaron (Journal of quantitative criminology, 2022)
Objectives For more than one hundred years, street lighting has been one of the most ubiquitous capital investments in public safety. Prior research on street lighting is largely limited to ecological studies of very small geographic areas, creating substantial challenges with respect to both causal identification and statistical power. We address limitations of the prior literature by studying a natural experiment created by short-term disruptions to municipal street lighting. Methods We leverage a natural experiment created by the differential timing of the repair of nearly 300,000 street light outages in Chicago. By conditioning on street segment fixed effects and focusing on a short window of time around the repair of a street light outage, we can credibly rule out confounding factors due to area-specific time trends as well as street segment-level correlates of crime. Results We find that outdoor nighttime crimes change very little on street segments affected by street light outages, but that outages cause crime to spill over to nearby street segments. Effects are largest for robberies and motor vehicle theft. Conclusions Despite strong environmental and social characteristics that tend to tie crime to place, we observe that street light outages are sufficiently salient to disrupt longstanding patterns. While the impact of localized street light outages can reverberate throughout a community, the findings imply that improvements in lighting can be defeated by the displacement of crime to adjacent spaces and therefore do not necessarily suggest that localized investments in municipal street lighting will yield a large public safety dividend.